Identification of Physiological Race Nematode, Radopholus similisCobb. that Attack Coffee Trees - Retno Hulupi (Indonesian Coffee and Cocoa Research Institute, 2006)
Physiological races of Radopholus similis Cobb., the burrowing nematode that attack coffee trees have never been reported yet, while two physiological races have been identified, i.e. banana and citrus races. Banana and citrus are commonly used as the shading trees or crop diversification in coffee plantation. Therefore, both races have to be analyzed whether the same as the race that attacking the coffee plants. Research to investigate the physiological race of R. similis Cobb. had been conducted in the screen house at Indonesian Coffee and Cocoa Research Institute, Jember. The experiment was arranged in randomized complete design with three replications, while cross inoculation tests were used as race identification method, by using three isolates from banana, citrus and Arabica coffee as the control. Tested host plants were banana Cavendish, ‘Ambon Kuning’ and ‘Raja’ varieties, rootstock of citrus Siam from Kintamani and Arabica coffee Kartika 1 variety. The expression of virulence of three nematode isolates against banana, citrus or arabica coffee tested to be considered as favorable host, while the most virulent isolate attacked coffee could be decided as physiological race of coffee. Results showed that banana isolate penetrated and attacked the roos of arabica coffee. The isolate of R. similis from citrus could not attack both coffee and banana varieties. Therefore, the physiological race of coffee was considered similar with the banana race. It was possible that the physiological race was specific race but it could attacke banana as other favorable host, however, it could not be proven in this results. Based on this results, the use of Musa sp.as intercrop or shade tree in coffee plantation has more risk to nematode attack than that of Citrus sp. Key words: physiological race, Radopholus similis, coffee, banana, citrus, nematode.